Hydrogen-induced program threshold voltage degradation analysis in SONOS wafer. (February 2016) - Lin, Qing; Zhao, Crystal; Sheng, Nan
Highlights: The hydrogen-induced V TP degradation is analyzed for SONOS memory. The H + accumulated in ONO stack is analyzed for V TP degradation. There are two ways to minimize V TP degradation during fabrication process. Re-sort test could effectively recover V TP failure from sort test point of view. Abstract: This paper studies the hydrogen-induced program state threshold voltage degradation in SONOS wafers, which ultimately impacts wafer sort test yield. During wafer sort step, all individual integrated circuits noted as die are tested for functional defects by applying special test patterns to them. The proportion between the passing die (good die) and the non-passing die (bad die) is sort yield. The different N2 /H2 ratio in IMD1 alloy process yields differently at flash checkerboard test. And the SIMS curves were also obtained to depict the distribution profile of H + in SONOS ONO stack structure. It is found that, the H + accumulated in the interface between the Tunnel oxide and Si layer, contributes the charge loss in Oxynitride layer, which leads to the program threshold voltage degradation and even fall below lower specification limit, and then impacts the sort yield of SONOS wafers.